Distribution, habitats, and redescription of the rare mite species Iphidonopsis sculptus Gwiazdowicz, 2004 (Mesostigmata: Ascidae) - Makarova, Olga L.; Marchenko, Irina I.; Lindquist, Evert E. (Zootaxa, 2021)
Iphidonopsis sculptus Gwiazdowicz, 2004, is currently known only from the type locality in eastern Poland and a record in southwestern Finland (Huhta, 2016). Here, we record this species from twelve localities elsewhere (Europe, Siberia, Far East of Russia, Canada) indicating its broadly Holarctic geographical range. Another genus member, Iphidonopsis magnanalis (Ma & Yin, 1999), is known only from China. About half of Iphidonopsis sculptus records are associated with litter of coniferous or mixed forests, but the others, including samples with juveniles (deutonymphs), were found in bracket fungi or under tree bark. The finding of two adult females on a bark beetle, Dryocoetes affaber (Mannerheim) (Coleoptera: Curculionidae: Scolytinae), suggests a phoretic association, though members of the closely related genus Zerconopsis Hull, 1918 as well as of all of the subfamily Arctoseiinae are known only from phoretic dispersal by nematoceran dipterans. The morphology of adults and an immature instar (deutonymph) of I. sculptus is redescribed and newly described, respectively, and illustrated in detail. A subdivision of the subfamily Arctoseiinae Evans, 1963 into three tribes is proposed—Arctoseiini Evans, 1963 (including Arctoseius Thor, 1930 and Iphidozercon Berlese, 1903), Zerconopsini tribe n. (Zerconopsis Hull, 1918; Xenoseius Lindquist & Evans, 1965; and Iphidonopsis Gwiazdowicz, 2004), and Maxiniini tribe n. (Maxinia Lindquist & Makarova, 2012).